2014
DOI: 10.1097/sla.0b013e3182a626f2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Aryl Hydrocarbon Receptor in Interleukin-23-Dependent Restoration of Interleukin-22 Following Ethanol Exposure and Burn Injury

Abstract: Objectives T-helper (Th)-17 lymphocytes play a crucial role in maintenance and regulation of gut immunity. Our laboratory has demonstrated that acute ethanol (EtOH) exposure before burn injury results in intestinal T cell suppression and enhanced bacterial translocation. Background To extend these studies, we examined the effects of EtOH exposure and burn injury on Th17 responses within intestinal lymphoid Peyer’s patches (PP). We further investigated whether restitution of interleukin (IL)-23 enhances PP ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 56 publications
6
21
0
Order By: Relevance
“…However, IL-17 levels were not significantly influenced by IL-23 restitution, suggesting that IL-23 differentially regulates IL-17 and IL-22 following ethanol and burn injury. Furthermore, our data demonstrate a role for AHR in IL-23-mediated restoration of IL-22, and indicate that AHR may be involved in the well-described IL-23/ROR-γt pathway (123; 144). Recent studies demonstrate that AHR may interact with multiple signaling molecules, including STAT proteins and members of the ROR family (189; 191).…”
Section: Potential Signaling Mechanisms Of T Cell Differentiationsupporting
confidence: 58%
See 1 more Smart Citation
“…However, IL-17 levels were not significantly influenced by IL-23 restitution, suggesting that IL-23 differentially regulates IL-17 and IL-22 following ethanol and burn injury. Furthermore, our data demonstrate a role for AHR in IL-23-mediated restoration of IL-22, and indicate that AHR may be involved in the well-described IL-23/ROR-γt pathway (123; 144). Recent studies demonstrate that AHR may interact with multiple signaling molecules, including STAT proteins and members of the ROR family (189; 191).…”
Section: Potential Signaling Mechanisms Of T Cell Differentiationsupporting
confidence: 58%
“…Furthermore, there are significant decreases in intestinal IL-22, RegIIIβ and RegIIIγ expression, which are accompanied with increases in intestinal permeability and bacterial overgrowth in animals receiving ethanol intoxication combined with burn injury. Treatment of animals with rIL-22 normalizes the expression of RegIIIβ and RegIIIγ in the small intestine, and prevents the increase in intestinal permeability, as well as reduces intestinal bacterial growth following ethanol and burn injury (123; 144). Together, these findings suggest that Th17 cells play a critical role in the maintenance of the intestinal mucosal barrier and immune responses after ethanol and burn injury.…”
Section: Th17 Effector Functionsmentioning
confidence: 99%
“…We have previously established that IL-22 production from T cells in gut associated lymphoid tissue (GALT) is significantly reduced following the combined injury(9). In addition, administration of recombinant IL-22 was shown to reduce intestine leakiness, suggesting that IL-22 may be beneficial following acute injury(8).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have demonstrated that approximately half of patients admitted to burn units have detectable blood ethanol levels, and that these patients exhibit higher rates of infection and greater incidence of mortality (6, 7). We have shown that ethanol intoxication exacerbates the suppression of intestinal T cells and potentiates small bowel barrier disruption, and increases Gram-negative bacterial overgrowth within one day after burn injury (8, 9). More recently, we have discovered changes to the microbiome in our rodent model of burn injury directly reflect the changes observed to the microbiome of hospitalized burn patients (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation